Comparison of Efficacy of Lactulose with and without Polyethylene Glycol in the Treatment of Patients with Hepatic Encephalopathy - Furqan Tahir, Irfan Younus, Zaid Gul, Adnan Qadir, Muhammad Bilal, Talha Firoz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the effectiveness of the combination of Lactulose and Polyethylene glycol (PEG) versus Lactulose alone in improving the grade of hepatic encephalopathy (HE) within 24 hours of hospital admission in patients with hepatic encephalopathy due to decompensated liver cirrhosis precipitated by constipation. Study Design: Randomized controlled trial. Place and Duration: The Department of Gastroenterology, Hepatology and GI Endoscopy, Shaheed Zulfiqar Ali Bhutto Medical University, Pakistan Institute of Medical Sciences (PIMS), Islamabad, Pakistan from 07-05-2020 to 06-05-2021. Methodology: One hundred and sixteen patients (58 in each group) of either gender aged 20-70 years having decompensated liver cirrhosis with HE grade 2 to 4 secondary to constipation were enrolled. Patients were randomly and equally divided into either Lactulose and PEG (Group-1) or Lactulose alone (Group-2) by lottery method. West Haven Criteria was used for labeling HE grades at the baseline and after 24 hours of treatment in both study groups. A one-grade improvement in HE after 24 hours of treatment from the baseline was considered as effectiveness of treatment. Results: Treatment was found effective (at least one HE grade improvement) in 43 (74.1%) patients treated with PEG+Lactulose, while it was 32 (55.2%) in patients who were treated with Lactulose alone (p=0.033). When stratified for age and gender, PEG+Lactulose was significantly effective in improving HE grades in younger age group (p=0.007) and males (p=0.040). Practical Implications: Combination treatment with PEG+Lactulose can be a preferred option for improvement in HE grades in comparison to treatment with lactulose alone Conclusions: Combination treatment with PEG+Lactulose was found to be more effective in improving HE grades when compared to treatment with lactulose alone within 24 hours of hospital admission among patients who had decompensated liver cirrhosis precipitated by constipation. Keywords: Constipation, decompensated liver disease, Hepatic encephalopathy, Lactulose, Polyethylene glycol.